Penerapan Terapi Benson untuk Mengurangi Nyeri pada Pasien Post Operasi Fraktur di RSUD Kajen Kabupaten Pekalongan - Indah Permata Sari; Dwi Retnaningsih; Rahayu Winarti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Post-fracture surgery patients generally experience acute pain due to damage to bone, muscle, and soft tissue affected by surgical trauma. Untreated pain can cause mobility disorders, anxiety, and even slow the healing process. Pain management can be carried out pharmacologically and non-pharmacologically. One effective non-pharmacological intervention is Benson relaxation therapy, a breathing relaxation technique combined with elements of belief or positive affirmations to create a sense of calm and comfort. The purpose of this case study is to determine the application of Benson relaxation therapy in reducing pain in post-fracture surgery patients at Kajen Regional Hospital, Pekalongan Regency. The method used is a descriptive case study approach, involving four post-fracture surgery patients who experienced pain with a scale of 4–6 (moderate pain). The instruments used include the Benson relaxation SOP, a Numeric Rating Scale (NRS) pain observation sheet, and a respondent consent form (informed consent). This case study was conducted in the inpatient ward of Kajen Regional Hospital, Pekalongan Regency, from September 8–13, 2025. Results showed a decrease in the average pain scale from 4–6 to 2–4 after 15 minutes of Benson relaxation therapy. Conclusion: Benson relaxation therapy effectively reduces pain intensity in post-fracture surgery patients and can be recommended as a non-pharmacological intervention in pain management in the ward.